PLACING WOMEN INTO THE HISTORY: DANCERS AND MUSICIANS AS REPRESENTED IN THE PALM LEAF PAINTING OF MEDIEVAL ODISHA - Malik, Sankarsan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Painting is an integral part of historical studies. In order to comprehend medieval women’s history, it is essential to rely on paintings as there are insufficient sources related to the subject. Studying medieval Orissa, particularly women’s history in Orissa, is challenging due to a shortage of sources and neglect towards women’s history. Medieval painting is considered the most vital and rich historical source. Like literature, painting of the periods also holds the same value as archaeological evidence for historical reconstruction. The social and cultural aspects of society were represented in the paintings of that period. Medieval women were renowned for their contributions to music and dancing. The advancement of musical and dancing culture in ancient and medieval Orissa was largely due to the contribution of women. Palm leaf paintings, stone sculptures, and mural paintings have depicted them with clear visibility. The palm leaf paintings of medieval Orissa, which were produced in large numbers during these periods, depict women’s talents and skill in playing musical instruments and dancing. This paper is intended to examine the role and status of women in society through the examination of palm leaf paintings from the medieval period.